Radiographic analysis of 1000 cast posts in Sergipe state, Brazil - Caroline Garcez MENDONÇA; José Rogério Vieira de ALMEIDA; Wilton Mitsunari TAKESHITA; Fábio MARTINS; Monica Silveira PAIXÃO (Universidade Estadual Paulista, 2017)
Abstract Introduction Endodontically treated teeth with extensive coronary destruction require posts and cores to enable prosthetic restoration. Despite the increasing use of prefabricated posts, cast metal posts and cores are still widely used. The quality of the latter is important for the longevity of restorative treatment, and failure can occur if the fundamental principles are not followed. Objective To radiographically evaluate the prosthetic principles of 1000 cast metal post-and-core restorations performed in single-rooted teeth and their coherence with the principles used for their confection. Material and method Digital periapical radiographs of 1000 endodontically treated, single-rooted teeth with cast metal posts and cores were selected from the collection of a radiology clinic (Centro de Imagem, Aracaju/SE, Brazil). The images were analyzed using a measurement software (ImageJ, USA) in accordance with the fundamental prosthetic principles: length and diameter of the post, ratio between post and bone crest, contiguity of post to the root canal, gap between post and the remaining root canal filling, amount of remaining root canal filling, and absence of periapical lesion. The data were qualitatively analyzed, classified into ideal and not ideal, and submitted to the chi-square test (α=0.05). Result Only 6.7% of the cast metal posts analyzed were satisfactorily fabricated. Conclusion Many prosthetic criteria are neglected during the manufacturing of cast metal post and cores, resulting in inadequate work that may compromise the longevity of restorative treatments.